Kajian Inklusivitas dalam Prespektif Green Social Work - Ramdani, Jaka (Jurnal Publisitas, 2025)
This study aims to analyze the relevance and potential application of the Green Social Work (GSW) approach in supporting inclusive and sustainable development in Jakarta Province. The research employed a systematic literature review method using a qualitative approach. Literature was selected through the keywords "Green Social Work," "social-ecological justice," "inclusive development," and "urban resilience" across databases such as Scopus, Web of Science, and Google Scholar, filtered based on inclusion criteria: publications from 2015 to 2025, scholarly articles, academic books, policy documents, and sources written in English or Indonesian. Data were analyzed using thematic analysis to identify the linkage between GSW values and Jakarta's development dynamics. The findings reveal that GSW can bridge the gap between the needs of vulnerable groups and development policies, while strengthening adaptive social-ecological systems against climate risks and urbanization pressures. Recommendations include mainstreaming GSW into regional planning, enhancing the capacity of social workers, strengthening community participation, and developing community-based social-ecological data systems. Thus, GSW can serve as a strategic framework for building Jakarta as a resilient, just, and sustainable city.